2019
DOI: 10.14740/jocmr3914
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Cardio-Ankle Vascular Index and Pulsatility Index of the Common Carotid Artery in Patients With Cardiovascular Risk Factors

Abstract: Background Pulsatility index (PI) is a hemodynamic parameter determined using Doppler sonography; it reflects the degree of peripheral vascular resistance. Moreover, researchers have reported significant relationships between an increase in the PI of the common carotid artery (CCA) and ischemic stroke. This cross-sectional study aimed to clarify the relationships between cardio-ankle vascular index (CAVI) as a marker of arterial stiffness and the PI of the CCA in patients with cardiovascular risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Inserting an intraarterial catheter is the most accurate method of assessing pulsatile hemodynamics, however, multiple studies indicated that non-invasive methods could be reasonable surrogates for invasive ones 31 33 . Hemodynamic parameters including blood velocities such as PSV, EDV, and MFV as well as PI and RI were used to study their clinical correlation with different cardiovascular conditions including but not limited to stroke 34 39 , hypertension 40 42 , arterial stenosis 43 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Inserting an intraarterial catheter is the most accurate method of assessing pulsatile hemodynamics, however, multiple studies indicated that non-invasive methods could be reasonable surrogates for invasive ones 31 33 . Hemodynamic parameters including blood velocities such as PSV, EDV, and MFV as well as PI and RI were used to study their clinical correlation with different cardiovascular conditions including but not limited to stroke 34 39 , hypertension 40 42 , arterial stenosis 43 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported that carotid atherosclerosis, which is evaluated through carotid artery ultrasonography, can indicate systemic atherosclerosis and be used as a predictor of CVD events [ 20 , 28 , 29 ]. However, several researchers have indicated significant associations between the CAVI and parameters of carotid artery ultrasonography [ 30 - 32 ]. The findings of the present study also indicated that the max-C-IMT, one of the parameters for carotid atherosclerosis, was significantly associated with the CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, low common carotid artery (CCA) PSV, and EDV are independently associated with cardiovascular disease (CVD) and events (e.g., stroke, heart disease) (Chuang et al, 2011(Chuang et al, , 2016; high internal carotid artery (ICA) PSV contributes to predict and grade ICA stenosis (Tokunaga et al, 2016); and low common femoral artery (CFA) PSV is predictive of ipsilateral iliac occlusion (Shaalan et al, 2003). On the other hand, CCA PI, and RI are associated with the prevalence of cerebral atherosclerosis and cardiovascular events (e.g., ischemic stroke) (Hitsumoto, 2019), ICA PI is associated with the global burden of small vessels disease (Lau et al, 2018), and CFA PI contributes to detecting peripheral vascular disease (Clifford et al, 1981). In turn, ICA/CCA velocity ratios contribute to detect and define arterial stenosis (Kochanowicz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%